Pemetaan Communication Assets Kelompok UMKM Apartemen Transit Ujungberung - Wulandari, Astri; Pramesthi, Jasmine Alya; Priastuty, Chairunnisa Widya; Nugroho, Catur (MENARA RIAU, 2024)
The challenges of Micro, Small and Medium Enterprises (MSMEs) today are getting higher. The development of digital technology that continues to be present certainly adds to the excitement of MSMEs themselves to continue to survive and continue to innovate. One of the interesting things, residents of the Ujung Berung Transit Apartment, especially young mothers, also participate in the development of MSMEs in Indonesia, especially in West Java. It's just that there are still many opportunities and gaps that have not been utilized, especially in relation to digital optimization, which needs to be highlighted in developing the capabilities of the UMKM actors of the Ujung Berung Transit Apartment. Through an approach in the form of a Focus Group Discussion (FGD) conducted to map the problems that occur in the Ujung Berung Transit Apartment, it is certainly a provision and foundation in conducting many programs and training for future community service, especially in relation to the use and optimization of social media. This will later be useful to equip the UMKM players of the Ujung Berung Transit Apartment to be literate in digital marketing and be able to spread their wings to a wider area without being hindered by place and location.